2021
DOI: 10.1111/eva.13286
|View full text |Cite
|
Sign up to set email alerts
|

Genomic signatures of artificial selection in the Pacific oyster, Crassostrea gigas

Abstract: The Pacific oyster, Crassostrea gigas , is an important aquaculture shellfish around the world with great economic and ecological value. Selective breeding programs have been carried out globally to improve production and performance traits, while genomic signatures of artificial selection remain largely unexplored. In China, we performed selective breeding of C . gigas for over a decade, leading to production of several fast‐growing strains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 91 publications
1
9
0
Order By: Relevance
“…By exploiting a new flat oyster genome, we demonstrated that nearly all consistent outliers are located on OE‐C8, spanning a region of 29.44 Mb and that half of the suggestive ones also mapped at OE‐C8, but population data suggest that this region could span 33.83 Mb, nearly half of OE‐C8. Previous studies suggested quick dropping of LD with physical distance in molluscs, especially in the wild, associated with their typical large effective population sizes (Gutiérrez et al, 2017; Hu et al, 2021; Vera et al, 2022; Zhong et al, 2017). In edible cockle ( Cerastoderma edule ), a species with an overlapping distribution and similar life‐history features to flat oyster, Vera et al (2022) detected a maximum r 2 of 0.05, which was significant at distances below 50 kb.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…By exploiting a new flat oyster genome, we demonstrated that nearly all consistent outliers are located on OE‐C8, spanning a region of 29.44 Mb and that half of the suggestive ones also mapped at OE‐C8, but population data suggest that this region could span 33.83 Mb, nearly half of OE‐C8. Previous studies suggested quick dropping of LD with physical distance in molluscs, especially in the wild, associated with their typical large effective population sizes (Gutiérrez et al, 2017; Hu et al, 2021; Vera et al, 2022; Zhong et al, 2017). In edible cockle ( Cerastoderma edule ), a species with an overlapping distribution and similar life‐history features to flat oyster, Vera et al (2022) detected a maximum r 2 of 0.05, which was significant at distances below 50 kb.…”
Section: Discussionmentioning
confidence: 97%
“…(Di et al, 2015;Gallaga-Maldonado et al, 2020;Maynard et al, 2016), sometimes involving specific immune genes, such as the histocompatibility complex (MHC; Kekäläinen et al, 2009;Penn et al, 2002). It is important to note that the term resistance applied until now in this and previous studies related to bonamiosis infection is rather inaccurate, as the response to the parasite may be related both to resistance against infection and the ability to survive once infected (tolerance) (Holbrook et al, 2021) in the wild, associated with their typical large effective population sizes (Gutiérrez et al, 2017;Hu et al, 2021;Vera et al, 2022;Zhong et al, 2017). In edible cockle (Cerastoderma edule), a species with an overlapping distribution and similar life-history features to flat oyster, Vera et al (2022) detected a maximum r 2 of 0.05, which was significant at distances below 50 kb.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, conserved synteny and chromosomal architecture against an independently assembled flat oyster genome assembly (Boutet et al, 2022), coupled with the general high congruency of the assembled super-scaffolds with linkage groups, further confirmed the global quality of our assembly. Expansions to gene families involved in stress responses during bivalve evolution may reflect adaptation to a filter-feeding sessile lifestyle in a hostile environment (Guo et al, 2018; Regan et al, 2021; Hu et al, 2022). Past work has revealed expansions in gene families encoding heat shock proteins, as well as families involved in apoptosis inhibition and innate immunity, including C-type lectins and C1q complement domain containing proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that, strictly speaking, the CN population is not a wild population, but has been subjected to unintentional artificial selection. Therefore, irrespective of whether we are referring to the AY-1 population or the CN population, the LD attenuation distance is shorter than that of other domesticated aquatic animals (For example, Crassostrea Gigas, Nile Tilapia, Large Yellow Croaker, scallop) (Cádiz et al, 2020;Hu et al, 2022;Kon et al, 2021;Wang et al, 2021). Therefore, we speculate that the gene recombination frequency and genetic diversity of the current cultured A. japonicas populations in China are generally high.…”
Section: Genetic Diversity Analysis Of the Cultured Apostichopus Japo...mentioning
confidence: 91%